2015
DOI: 10.1248/bpb.b15-00183
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Reduces Nociceptive Responses in Mouse Orofacial Formalin Model: Potentiation by Sigma-1 Receptor Antagonist BD1047 without Impaired Motor Coordination

Abstract: Although the administration of clonidine, an alpha-2 adrenoceptor agonist, significantly attenuates nociception and hyperalgesia in several pain models, clinical trials of clonidine are limited by its side effects such as drowsiness, hypotension and sedation. Recently, we determined that the sigma-1 receptor antagonist BD1047 dose-dependently reduced nociceptive responses in a mouse orofacial formalin model. Here we examined whether intraperitoneal injection of clonidine suppressed the nociceptive responses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Peripheral neuropathic pain is produced by multiple etiological factors, and spared nerve injury (SNI) is an important model for exploring the cellular and molecular mechanism in peripheral neuropathic pain ( 1 , 2 ). It has been demonstrated that the agonists of α2-adrenoceptors (α2-AR) have anti-nociceptive effects ( 3 , 4 ). Tizanidine, a derivative of clonidine, is a highly selective agonist of α2-AR, and has the same effects of clonidine, but the side effects such as low arterial blood pressure and bradycardia are lower ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral neuropathic pain is produced by multiple etiological factors, and spared nerve injury (SNI) is an important model for exploring the cellular and molecular mechanism in peripheral neuropathic pain ( 1 , 2 ). It has been demonstrated that the agonists of α2-adrenoceptors (α2-AR) have anti-nociceptive effects ( 3 , 4 ). Tizanidine, a derivative of clonidine, is a highly selective agonist of α2-AR, and has the same effects of clonidine, but the side effects such as low arterial blood pressure and bradycardia are lower ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intraperitoneal administration of clonidine under formalin test responds in a similar dose dependent manner in mice and rats ( Yoon et al., 2015 ; Fukuda et al., 2006 ). Clonidine administration intrathecally also shows similar dose dependent responses under formalin test in the African marsh terrapin ( Pelomedusa subrufa ) and Speke's hinged tortoise ( Makau et al., 2014 , 2016 ); mice ( Kanui et al., 1993 ), and Sprague-Dawley rats ( Yoon et al., 2009 ).…”
Section: Discussionmentioning
confidence: 90%
“…The S1R is a non-opioid chaperone receptor located in the plasm membrane of the endoplasmic reticulum (Hayashi and Su, 2003) expressed in regions associated with pain regulation, such as dorsal root ganglia, spinal cord, thalamus, and rostroventral medulla of female mice (Sánchez-Fernández et al, 2014) and the spinal cord, thalamus, and sciatic of male rats (Alonso et al, 2000). S1R is reported in the trigeminal ganglia of male mice (Yoon et al, 2015), but expression in female trigeminal sensory neurons currently unknown. Activation of S1R elicits nociceptive responses, which can be reversed with SR1 antagonists (Kim et al, 2008;Gris et al, 2014;Parenti et al, 2014;Pyun et al, 2014;Roh and Yoon, 2014;Tejada et al, 2014;Entrena et al, 2016) or in S1R knockout mice (Entrena et al, 2009;de la Puente et al, 2009).…”
Section: Discussionmentioning
confidence: 99%